Growth inhibition of pancreatic cancer cells by histone deacetylase inhibitor belinostat through suppression of multiple pathways including HIF, NFkB, and mTOR signaling in vitro and in vivo. Issue 9 (8th March 2013) - Chien, Wenwen; Lee, Dhong Hyun; Zheng, Yun; Wuensche, Peer; Alvarez, Rosie; Wen, Ding Ling; Aribi, Ahmed M.; Thean, Su Ming; Doan, Ngan B.; Said, Jonathan W.; Koeffler, H. Phillip
Abstract Pancreatic ductal adenocarcinoma is a devastating disease with few therapeutic options. Histone deacetylase inhibitors are a novel therapeutic approach to cancer treatment; and two new pan‐histone deacetylase inhibitors (HDACi), belinostat and panobinostat, are undergoing clinical trials for advanced hematologic malignancies, non‐small cell lung cancers and advanced ovarian epithelial cancers. We found that belinostat and panobinostat potently inhibited, in a dose‐dependent manner, the growth of six (AsPc1, BxPc3, Panc0327, Panc0403, Panc1005, MiaPaCa2) of 14 human pancreatic cancer cell lines. Belinostat increased the percentage of apoptotic pancreatic cancer cells and caused prominent G2/M growth arrest of most pancreatic cancer cells. Belinostat prominently inhibited PI3K‐mTOR‐4EBP1 signaling with a 50% suppression of phorphorylated 4EBP1 (AsPc1, BxPc3, Panc0327, Panc1005 cells). Surprisingly, belinostat profoundly blocked hypoxia signaling including the suppression of hypoxia response element reporter activity; as well as an approximately 10‐fold decreased transcriptional expression of VEGF, adrenomedullin, and HIF1α at 1% compared to 20% O2. Treatment with this HDACi decreased levels of thioredoxin mRNA associated with increased levels of its endogenous inhibitor thioredoxin binding protein‐2. Also, belinostat alone and synergistically with gemcitabine significantly (P = 0.0044) decreased the size of human pancreatic tumors grown in immunodeficiency mice. Taken together, HDACi decreases growth, increases apoptosis, and is associated with blocking the AKT/mTOR pathway. Surprisingly, it blocked hypoxic growth related signals. Our studies of belinostat suggest it may be an effective drug for the treatment of pancreatic cancers when used in combination with other drugs such as gemcitabine. © 2014 Wiley Periodicals, Inc.